Sistema de indicadores para un modelo de gestión sostenible en emprendimientos turísticos en las comunidades de la Costa Norte de Manabí - Arturo Solorzano, Erika Pierina (2020)
The objective of this research was to design an indicator system that contributes as an intervention tool for a sustainable management model in tourist ventures in communities on the north coast of Manabí; For its scope, 4 specific objectives were defined focused on (1) characterizing the tourist communities, (2) evaluating the management of the actors involved, (3) outlining management strategies and (4) outlining the system of sustainable management indicators. The methodology responds to 4 phases determined by 8 methodological references, among which the traffic light technique taken from the Secretary of Tourism of Mexico stands out; The research is of an exploratory type carried out through field work and the use of the Delphi methodology that validated the proposed indicators. It was determined that in the study area there are 7 communities with potential for community tourism; However, the management by the actors involved is very poor due to disjointed work, which is why the sustainable development of these ventures is deteriorating. To mitigate this problem, the Canvas Business Model was established as a strategy for the adequate planning of the ventures. The system of indicators that was designed responds to the determined environmental, socio - cultural and economic - business fields. It is concluded that the disarticulated management between the involved actors radically affects the tourist development of this area; In addition to this, the scarce application and promotion in the use of sustainable indicators makes tourism management difficult.